The Progression of Experimental Design and Data Analysis in Applied Behavior Analysis. Issue 2 (3rd July 2021) - Rader, Allie E.; Rader, Kevin A.; Katz, Jodi S.; Leaf, Justin B.
ABSTRACT: Single subject design and visual analysis have become the standard for conducting and interpreting research in Applied Behavior Analysis (ABA). These methods can be traced in behavioral literature from the early 1900s and were revolutionized by Skinner's philosophy of radical behaviorism. This ultimately led to a divergence in methods between behaviorism and the rest of psychology. Skinner's divergence from conventional methods of research (group design and statistical analysis) may have historical underpinnings. His unique methods and philosophy led to the establishment of the Experimental Analysis of Behavior (EAB), Applied Behavior Analysis (ABA) and the Journal of Applied Behavior Analysis (JABA). The prevalence of conventional methods of research in behavior analytic literature remains unknown. Therefore, the purpose of this paper is to (1) report the history of research methods and data analysis in ABA and JABA and (2) analyze trends in methods within JABA to determine whether they are progressive.